Proposal for an e-learning system model based on the invocation and semantic discovery of web services - Halim, Mohamed; Tahiri, Abdelmajid; El Ghzizal, Yassir; Adadi, Nouha; Chenouni, Driss (Indonesian Journal of Electrical Engineering and Computer Science, 2024)
Service-oriented computing (SOC) provides a new framework for designing distributed web applications and software in a flexible, scalable, and cost-effective manner. Its use is widespread to efficiently integrate existing Web services and create high value-added applications. This model, proven in various fields such as e-commerce, also shows significant advantages in the field of e-learning. This approach highlights the discovery and use of Web services listed in specialized directories. In fact, this paper proposes a framework for exploring web services associated with education. This approach is based on the application of a matching algorithm to select the services best suited to the needs of users of the online learning system, as well as the ontology of the e-learning domain and the semantic descriptions of the web services via web ontology language for web services (OWL-S).